2013
DOI: 10.5539/jfr.v2n3p104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry for Rapid Identification of Bacteria in Processed Soybean Products

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has recently been demonstrated as a rapid and reliable method for identifying bacteria in colonies grown on culture plates. Rapid identification of food spoilage bacteria is important for ensuring the quality and safety of food. To shorten the time of analysis, several researchers have proposed the direct MALDI-TOF MS technique for identification of bacteria in clinical samples such as urine and positive blood cultures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…E. coli could be correctly identified when present at a minimum of 10 7 CFU/mL (Table 2). This result indicates an improvement in the identification limit was obtained compared to previous results (Furukawa et al, 2013). K. pneumoniae and C. freundii could also be identified with adequate identification scores when present at the same concentration (data not shown).…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…E. coli could be correctly identified when present at a minimum of 10 7 CFU/mL (Table 2). This result indicates an improvement in the identification limit was obtained compared to previous results (Furukawa et al, 2013). K. pneumoniae and C. freundii could also be identified with adequate identification scores when present at the same concentration (data not shown).…”
Section: Resultsmentioning
confidence: 49%
“…After anionic surfactant treatment (0.5% SDS), accurate identification scores were obtained using soy milk samples with up to 70% fat content (Table 1). When using a previously described method for removing proteins from soy milk (Furukawa et al, 2013), MALDI-TOF MS scores were less than 2.0 when the fat content of soy milk samples was 50% and greater. This indicated that residual fat matrices may have interfered with the raw mass spectra and affected spectrum matching.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, it is difficult to detect and identify bacteria in high lipid-containing food. Moreover, little information is available on non-culture based bacterial identification in food samples using the MALDI-TOF MS (Barreiro et al, 2012;Ferreira et al, 2010;Furukawa et al, 2013;Katase & Tsumura, 2014).…”
Section: Introductionmentioning
confidence: 99%